2013
DOI: 10.1021/ma301730n
|View full text |Cite
|
Sign up to set email alerts
|

Linear Viscoelasticity of Polyelectrolyte Complex Coacervates

Abstract: Two flexible, oppositely charged polymers can form liquid-like complex coacervate phases with rich but poorly understood viscoelastic properties. They serve as an experimental model system for many biological and man-made materials made from oppositely charged macromolecules. We use rheology to systematically study the viscoelastic properties as a function of salt concentration, chain length, chain length matching, and mixing stoichiometry of model complex coacervates of poly(N,N-dimethylaminoethyl methacrylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
371
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(416 citation statements)
references
References 36 publications
(111 reference statements)
44
371
1
Order By: Relevance
“…Rheological characterization demonstrated that these trends correlate with decreasing coacervate viscosity with increasing salt concentration ( Figure 5a) [71,79,157]. Furthermore, the viscosity was seen to increase as a function of degree of polymerization ( Figure 5b) [79], as would be expected for polymeric materials. Inspection of the data in Figure 5 suggests that viscosity varies exponentially with salt concentration, and follows a power-law behavior as a function of polymer chain length.…”
Section: Viscositymentioning
confidence: 58%
See 4 more Smart Citations
“…Rheological characterization demonstrated that these trends correlate with decreasing coacervate viscosity with increasing salt concentration ( Figure 5a) [71,79,157]. Furthermore, the viscosity was seen to increase as a function of degree of polymerization ( Figure 5b) [79], as would be expected for polymeric materials. Inspection of the data in Figure 5 suggests that viscosity varies exponentially with salt concentration, and follows a power-law behavior as a function of polymer chain length.…”
Section: Viscositymentioning
confidence: 58%
“…In general, the trends observed in frequency sweep data parallel those for viscosity, due to the relationship between dynamic viscosity and modulus. In general, increasing salt concentration leads to a decrease in both the storage and loss modulus (Figure 7a) [71,75,79]. Similarly, changes in pH that weaken the electrostatic interactions between polymer chains also decrease the moduli (Figure 7b) [75].…”
Section: Frequency Sweepsmentioning
confidence: 96%
See 3 more Smart Citations